English Education Students' Perspective of English Learning Content on Instagram - Yogi Pratama; Susilawati Susilawati; Eline Rozaliya Winarto (National Conference on Language, Education, and Technology Proceeding, 2022)
This research aims to investigate students’ perspective of English learning content on Instagram and to investigate the impact of English education students’ perspective toward English learning content on Instagram. This research employed qualitative research by using descriptive qualitative design. The instrument was used in this research is interview. The data were analyzed by using Miles and Huberman model. In this model, the researcher conducted three analytical activities data simultaneously, namely: (1) data reduction (2) data display and (3) conclusion drawing/verification. The research findings of this research show that English education students give positive perspective toward English learning content on Instagram. There are four things that indicate their positive perspective. Firstly, the benefits of the contents. Secondly, the improvement of English education students from the contents. Thirdly, the usefulness of English learning content on Instagram. Fourthly, English education students’ point of view towards English learning content. As a result of their positive perspective, there are three things that they reveal. Firstly, English learning content good for students. Secondly, Instagram as a learning media. Thirdly, the use of Instagram in teaching and learning activity.